Content of heavy metals in soils of Bidoup Nui Ba National Park (Southern Vietnam) - Pham, Cam Nhung; Lebedev , Yaroslav; Drygval, Anna; Gorbunov , Roman; Gorbunova, Tatiana; Kuznetsov, Andrey; Kuznetsova, Svetlana; Nguyen, Dang Hoi; Tabunshchik, Vladimir (Journal of Degraded and Mining Lands Management, 2024)
The study of technogenic pollution of soils with heavy metals (HM) is an essential task for ecology. The analysis of the content of HMs in the park's soils shows the degree of pollution and the sources of its occurrence. The study of the elemental composition of soils is an objective method for assessing the state of the ecosystem. To determine the current state of heavy metal contamination in forest soils, the concentrations of their total forms were analyzed. Heavy metals, including Zn, Pb, Cr, Cu, Hg, Cd, and As, were found in the study area. In addition, the threat of contamination with Cd and As has been identified. The calculation of the total pollution coefficient allows us to assess the level of pollution for the dry season (Zc = 18.45-28.24, average 22.45) as average (moderately hazardous) and for the wet season (Zc = 0.01-5.11, average 1.96) as permissible. This indicates an unfavorable environmental situation. The content of heavy metals in soils depends on the season. Observations show that at the end of the wet season, the concentration of heavy metals decreases, while it increases in the period after the dry season.